PENGARUH LINGKUNGAN KERJA DAN KOMPETENSI GURU TERHADAP KINERJA GURU DI GUGUS VI KECAMATAN SERIRIT - Kartika, Riana Dewi; Saputrayasa, Komang Dana (Komunitas Manajemen Kompetitif, 2023)
This study aims to determine the effect of the work environment on teacher performance in Cluster VI Seririt District and to determine the effect of teacher competence on teacher performance in Cluster VI Seririt District. The type of research in this study was quantitative, with a total population of 47 teachers and a sample of 18 male teachers and 29 female teachers for a total of 47 people. The data analysis technique used in this study is multiple linear regression analysis, classical assumption test, model feasibility test (goodness of fit) using the SPSS Version 21.0 application for windows. The results of this study indicate that the work environment has an effect on teacher performance in Cluster VI Seririt District of 0.468. The results of testing the hypothesis with the T-test found that t-test > t-table (2.753 > 1.677). This shows that the work environment has a significant positive effect on teacher performance seen from a significant level of 0.009 <0.05. Teacher competence has an effect on teacher performance in Cluster VI Seririt District of 0.363 with the results of testing the hypothesis with the T-Test it was found that t-count > t-table (2.670 > 1.677), this shows that teacher competence has a positive and significant influence